Some aspects of juvenile justice system reforming in Ukraine - Tereschuk, Galina (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article analyzes the main ways of reforming the juvenile justice system in Ukraine as an important element in the state mechanism of protection of minors today.